2015
DOI: 10.14581/jer.15003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Short-term Mortality of Status Epilepticus and Its Risk Factors

Abstract: Background and Purpose:Status epilepticus (SE) is defined as epileptic seizures of greater than five minutes or more than one seizure within a five minute period without returning to normal consciousness between them. It is a life-threatening condition particularly if treatment is delayed. Previous studies reported age, duration and etiology of SE as primary determinants of mortality.Methods:This prospective cross-sectional study performed on the patients with status epilepticus admitted in Rasoul-e-Akram hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The long-term outcome of 596 cases with refractory SE was analyzed by Ferlisi et al, the results of which indicated that 35 % of the patients had died, 13 % had a severe neurological deficit, and only 35 % recovered to baseline [ 33 ]. Recent prospective studies have also shown that refractory SE appeared to be strongly associated with poor outcomes [ 34 , 35 ]. Considering the controversy surrounding the definition of refractory SE, i.e., the number of AEDs that patients need to have failed and the duration of SE after the initiation of treatment [ 10 ], we chose several variables that reflect the features of refractory SE, including diazepam resistance, SE duration, use of three or more types of intravenous AEDs, a drug induced coma, and tracheal intubation, as candidate predictors when performing the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term outcome of 596 cases with refractory SE was analyzed by Ferlisi et al, the results of which indicated that 35 % of the patients had died, 13 % had a severe neurological deficit, and only 35 % recovered to baseline [ 33 ]. Recent prospective studies have also shown that refractory SE appeared to be strongly associated with poor outcomes [ 34 , 35 ]. Considering the controversy surrounding the definition of refractory SE, i.e., the number of AEDs that patients need to have failed and the duration of SE after the initiation of treatment [ 10 ], we chose several variables that reflect the features of refractory SE, including diazepam resistance, SE duration, use of three or more types of intravenous AEDs, a drug induced coma, and tracheal intubation, as candidate predictors when performing the statistical analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Moghaddasi found that patients with a history of epilepsy had higher mortality rates than those without. 30 Furthermore, Kang found that a history of epilepsy was associated with neurological sequelae to a further extent than a history of acute symptomatic SE. Our study identified a history of epilepsy to be an independent predictor of outcome in SE.…”
Section: Discussionmentioning
confidence: 99%
“…SE is a pathological condition in which the patient requires urgent hospitalization and emergency treatment. SE is associated with substantial morbidity and mortality [58,59]. SE has an incidence of up to 61 per 100,000 people per year and is divided into four sequential stages (early, established, refractory and super refractory) that are important in the pharmacotherapy of SE [60].…”
Section: Experimental Evidence Regarding the Anticonvulsant Action Ofmentioning
confidence: 99%